2016
DOI: 10.1016/j.jcrimjus.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of psychopathy measurement (PCL-R and SRP-III/SF) and recommendations for future research

Abstract: Purpose: The purpose of this paper was to review, summarize, and critically engage with the most recent findings into the dimensionality of the PCL-R, SRP-III, and SRP-SF. Another objective was to provide a set of directions for future research.Methods: A search in PubMed, PsychInfo, Scopus, Web of Science, Science Direct, and Google Scholar was performed. Twenty-one studies examining the dimensionality of the PCL-R and 11 studies assessing the factor structure of the SRP-III and SRP-SF were identified.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 94 publications
(135 reference statements)
4
64
1
Order By: Relevance
“…All correlations between four psychopathy factors were weak to moderate, except for the correlation between affective responsiveness and cognitive responsiveness (r = .50) facets, which indicates a significant overlap between the variables. As suggested by Boduszek and Debowska (2016), when the best model fit is multidimensional and some factors are highly correlated (.50 and above), a differential predictive validity test has to be conducted to verify whether the factors correlate differentially with external criteria. Table 5 presents the outcome of regression analyses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All correlations between four psychopathy factors were weak to moderate, except for the correlation between affective responsiveness and cognitive responsiveness (r = .50) facets, which indicates a significant overlap between the variables. As suggested by Boduszek and Debowska (2016), when the best model fit is multidimensional and some factors are highly correlated (.50 and above), a differential predictive validity test has to be conducted to verify whether the factors correlate differentially with external criteria. Table 5 presents the outcome of regression analyses.…”
Section: Resultsmentioning
confidence: 99%
“…As for the factor structure of the PPTS, Boduszek and Debowska (2016), in a critical evaluation of psychopathy measurement, indicated that it is unacceptable to assume that only one model exists for a particular scale and that competing solutions ought to be tested in order to fully explore the dimensionality of a measure. As per those recommendations, we tested seven different conceptually sound models of the PPTS, using confirmatory factor techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For psychopathic personality, the debate more specifically concerns to what degree antisocial and criminal behavior should be included in the conceptualization of the construct (Boduszekab & Debowskac, ; Storey, Hart, Cooke & Michie, ). There seems to be a general agreement that antisocial behavior is a part of psychopathic personality (Hare, Neumann & Mokros, ; Neumann, Hare & Pardini, ), however, the disagreement specifically concerns if criminal behavior is a core feature of psychopathy or should be considered a secondary or related feature (CAPP, ; Skeem & Cooke, , ).…”
Section: Introductionmentioning
confidence: 99%
“…() found more than 10 four‐factor models, including a four‐factor correlated model, a four‐factor hierarchical model and a two‐factor with four‐facet hierarchical model. Some models have parceled a subset of items and used these to indicate an overall psychopathy factor, and other studies have failed to report sufficient model fits to determine the most appropriate latent structure of the psychopathy construct (Boduszekab & Debowskac, ). The research literature suggests empirical support for superiority of the three‐factor (e.g., Cooke & Michie, ; Skeem, Mulvey & Grisso, ) and the four‐factor model, respectively (e.g., Bolt, Hare, Vitale & Newman, ; Hare & Neumann, ; Hare, )(Hare et al ., ).…”
Section: Introductionmentioning
confidence: 99%